2012
DOI: 10.1097/inf.0b013e31823f0e11
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Lipodystrophy in HIV–infected Children After Substitution of Stavudine With Zidovudine in a Non-nucleoside Reverse Transcriptase Inhibitor–based Antiretroviral Therapy

Abstract: Substitution of stavudine with zidovudine resulted in decreased severity or resolution of LD among HIV-infected children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
3
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 21 publications
11
56
3
6
Order By: Relevance
“…Contrary to our study, Aurpibul in Thailand had noticed that lipodystrophy was more common in girls than boys, 61% and 39% of cases respectively [5]. Actually, there are seemed to be gender-based physiological differences in the occurrence of lipodystrophy.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Contrary to our study, Aurpibul in Thailand had noticed that lipodystrophy was more common in girls than boys, 61% and 39% of cases respectively [5]. Actually, there are seemed to be gender-based physiological differences in the occurrence of lipodystrophy.…”
Section: Discussioncontrasting
confidence: 52%
“…In all these three researches mentioned above, study design included adolescents aged 18 years in whom the risk of occurrence of lipodystrophy is higher than that of under 15 years [5] [10] [11]. Other diagnostic methods are more accurate and should be used whenever possible; skin fold measurement or muscles Dexa-scan and body fat assessment [18] [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dearth of data on dysglycaemia among HIV-infected children, although a Thailand study revealed that about 4% had hyperglycaemia in a cohort of ART experienced children (non-PI based) 13 . Several studies [14][15][16][17] among HIV-infected Nigerian children have reported a high prevalence of malnutrition, diarrhoeal disease, pneumonia, septicaemia and malaria, all of which are known confounders of hypoglycaemia 18-22 and hyperglycaemia 18,23,24 outside the context of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…HIV pancreatic dysfunctions manifest clinically as hypoglycaemia and hyperglycemia [7][8][9][10][11][12][13][14][15] and are seen in both antiretroviral therapy (ART)-experienced and ART-naïve patients 11,12 . The mechanisms of HIV pancreatic dysfunctions include pancreatic infection by HIV and other opportunistic organisms including cytomegalovirus and toxoplasma 7 , infiltration of the pancreatic gland by malignancies 7 , and the effects of therapeutic interventions [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%